PENGARUH FUNDAMENTAL SALES TRAINING (FST) TERHADAP KINERJA KARYAWAN BAGIAN MARKETING PADA PT.AGUNGG AUTOMALL SUTOMO CABANG PEKANBARU - Indriyani, Weri; Farida, Lena (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Training (FST) Fundamental Sales Training should be of particular concern for the companyas HR in a company is one of the very important role to achieve success and goals of thecompany and therefore the employee first trained to be able to know the advantages anddisadvantages of the employee so that the employee can fix it before working to improvehuman resources better for the company training program (FST) Fundamental Sales Traininghas a significant impact on employee performance of marketing that will increase employee.This study aims to determine the effect of the program (FST) fundamental salestraining on employee performance of marketing PT.AGUNG Automall Sutomo pekanbarubranch. Obtained from a questionnaire with a number of respondents as many as 66 peopledip further by using descriptive statistics and then the is data presented in tabular format withthe numbers and percentages for subsequent analysis results show that the implementation ofthe training program FST has a considerable influence both the performance of employeesAutomall PT.AGUNG marketing division SutomoKeywords : training , employee performance